Pesticides in Science Education: the study in the field education - Carolina dos Santos Fernandes; Geovana Mulinari Stuani (Universidade Federal do Rio Grande do Sul, 2015)
This work aims to analyze and discuss the students' understandings of undergraduate course in Field Education of the Federal University of Santa Catarina (UFSC) on the thematic of pesticides in science teaching. To grasp the understandings of students it was applied an instrument in which the undergraduates were asked to writer about the importance of addressing the issue of pesticide in basic education. The analysis pointed out the need to understand the thematic of pesticides on broad aspects that corresponds conceptual contents from the area of Natural Science and Mathematics, as well as social, environmental, political, economics, ethnical and others aspects.